2006
DOI: 10.1590/s1516-35982006000600033
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de resíduo agroindustrial de abacaxi desidratado em dietas para caprinos em crescimento: digestibilidade e desempenho

Abstract: RESUMOUse of dehydrated pineapple by-product in diets for growing goats: digestibility and performance ABSTRACT -The objective of this study was to evaluate the effect of replacing coastcross (Cynodon dactylon) hay with a dehydrated pineapple by-product (DPB) on performance, apparent digestibility, and intake of digestible nutrients in growing goats. Twenty-four crossbred Saanen x Criola female goats averaging 19.2 kg of body weight (BW) at the beginning of the trial were used in a completely randomized design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 4 publications
1
0
0
14
Order By: Relevance
“…Feed conversion (FC) in this study varied from 4.93 to 5.57kg MS kg -1 of body weight gain, but with no influence of the level of glycerin inclusion in the diet. The results presented are similar to those described by CORREIA et al (2006), observed in crossbred female kid goats, Saanen x Crioula, feedlot and fed with pineapple agro-industrial residue, a FC varying from 5.62 to 5.97kg MS kg -1 of weight gain. The inclusion of up to 15% of glycerin in the DM of the diet had no effect on the exploitation and conversion of dry matter in body weight by the animals, corroborating the findings by SANTOS et al (2015).…”
Section: Resultssupporting
confidence: 89%
“…Feed conversion (FC) in this study varied from 4.93 to 5.57kg MS kg -1 of body weight gain, but with no influence of the level of glycerin inclusion in the diet. The results presented are similar to those described by CORREIA et al (2006), observed in crossbred female kid goats, Saanen x Crioula, feedlot and fed with pineapple agro-industrial residue, a FC varying from 5.62 to 5.97kg MS kg -1 of weight gain. The inclusion of up to 15% of glycerin in the DM of the diet had no effect on the exploitation and conversion of dry matter in body weight by the animals, corroborating the findings by SANTOS et al (2015).…”
Section: Resultssupporting
confidence: 89%
“…Efeito dos períodos de armazenamento do silo sobre a matéria seca (MS) da silagem de milho. Entretanto, ao avaliar o teor de MS, em função do tempo de abertura dos silos da silagem de milho, observa-se que essas variações foram pequenas, podendo ser decorrentes de respiração residual durante o enchimento e imediatamente após a vedação do silo, tipo de fermentação no interior do silo, produção de efluente ou fermentações secundárias por bactérias heterofermentativas, enterobactérias e leveduras durante o período de armazenagem que levam a perdas de matéria seca por gases (Evangelista et al, 2004).…”
Section: Dm (%)unclassified
“…Portanto, ambas as silagens em todos os tempos de fermentação apresentaram boa conservação da fração protéica (Tabela 3). Segundo Evangelista et al (2004), caso não se obtenha silagens estáveis com baixo pH, tem-se aumento da atividade clostridiana, responsável pela degradação da fração protéica. Assim, a boa conservação da fração protéica, observada para todas as silagens, pode estar relacionada com o baixo pH obtido e conseqüentemente, com uma redução ou ausência de fermentação clostridiana.…”
Section: Períodos De Armazenamento (Dias)unclassified
“…Para utilização do resíduo agroindustrial do abacaxi na alimentação animal torna-se conveniente estabelecer um equilíbrio entre os nutrientes da dieta para que haja fermentação eficiente no rúmen objetivando otimizar o crescimento microbiano e maximizar a digestão da fibra, atendendo às necessidades nutricionais dos ruminantes (Correia et al, 2006).…”
Section: Introductionunclassified